BE FAITHFUL IN CARRYING OUT OUR RESPONSIBILITIES - DR. CHANDRA MUZAFFAR - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
KUALA LUMPUR, 14 October 2016 – As an alumni member of an institution, regardless of our role or status in life, we need to contribute towards establishing a peaceful and blissful society.